Relations between Morocco and West Africa: Paths to SustainableDevelopment and Regional Integration (International Journal of Environmental Sciences, 2025)
AbstractThis literature review article summarizes the studies that have focused on the relations between Morocco and West Africancountries, leading to sustainable development and regional integration. But also, the article mentions two (02) points thathave not been studied, and which would also lead to sustainable development and regional integration for Morocco and WestAfrica. To carry out the study presented in this article, non-participant observation, documentary research and analysis, andtestimonies made it possible to identify works highlighting the historical context between Morocco and West Africa, economicand trade relations, political and diplomatic relations, security relations and strategic cooperation, as well as cultural andsocial ties focused on sustainable development and regional integration through relations between Morocco and West Africa.However, this literature review also identified, as missing points in previous research, sustainable development initiatives andprospects for regional integration through relations between Morocco and West Africa. These points, therefore, complementprevious studies. Indeed, sustainable development initiatives through relations between Morocco and West Africa have notbeen studied, which will allow Morocco to achieve its main objectives, namely its autonomy over the Sahara, allowing it toachieve a higher level of sustainable development due to the wealth that the Sahara abounds in and its leadership on theAfrican continent. These initiatives will allow West Africa, in turn, to experience sustainable development differently balancedand win-win with Morocco as a potential and new ideal partner in terms of cooperation, in several sectors such as oil, mining,industry, health, and security. The same applies to the prospects for integration through relations between Morocco and WestAfrica, which have not been studied, but which could give Morocco the opportunity to integrate West African sub-regionalcommunities